COVID-19 and Children in Senegal: Epidemiological and Virological Insights - Dia, Ndongo; Diagne, Moussa Moise; Fall, Gamou; Jallow, Mamadou Malado; Fall, Amary; Barry, Mamadou Alioune; Diallo, Amadou; Faye, Oumar; Dione, Marie Henriette Dior; Bop, Ndeye Sakha; et al. (Archives of Clinical and Biomedical Research, 2022)
Background: Children were less impacted by the COVID-19. Since its first case of COVID-19 on the 2nd of March 2020, Senegal has experienced 3 major epidemic waves with 1886 deaths reported. Here we aim to describe the epidemiology of SARS-COV-2 in Senegal, focusing on the pediatric population in order to appraise the specific virological and epidemic-ological characteristics of COVID-19 in this age stratum. Methods: From February 2020 to September 2021, 158,076 suspected patients were tested for COVID-19 diagnostic. Demographical information, clinical details and history of exposure were collected from patients by the clinicians. SARS-CoV-2 diagnostic results (positive/negative), Ct values, are entered into an electronic master database (updated daily). Results: Of these 12,535 (7.9%) were children under 15 years old. 1496 (11.9%) children were confirmed SARS-CoV-2 infected. Dakar was the most impacted region with 754 cases. SARS-CoV-2 positive cases per epidemic wave were distributed as follows: 846 (9.1%; 826/9287) in the 1st wave, 321 (15.8%; 321/ 2031) for the 2nd wave and 329 (27%; 329/1217) in the 3rd wave. We also noted lowest Ct values during the 3rd wave which coincides with the Delta variant emergence and dominance in Senegal. Indeed, the delta variant seems to have more resources for a more effective infection in children, including the very young children. Conclusion: In addition to a high overall SARS-CoV-2 confirmation rate, this study specially showed that the pediatric population was much more affected during the 3rd epidemic wave with a higher prevalence and also higher viral loads in children.